1997
DOI: 10.1074/jbc.272.17.11575
|View full text |Cite
|
Sign up to set email alerts
|

A Two-site Model for ApoB Degradation in HepG2 Cells

Abstract: Newly synthesized apolipoprotein B (apoB) undergoes rapid degradation in a pre-Golgi compartment in HepG2 cells. A major site of this early degradation seems to be on the cytosolic side of the endoplasmic reticulum (ER) membrane and is sensitive to N-acetylleucinyl-leucinyl-norleucinal (ALLN), which can inhibit neutral cysteine proteases and/or proteasome activity. Oleate (OA) treatment, which facilitates translocation of nascent apoB across the ER membrane, also reduces early degradation. In the present studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
71
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 31 publications
6
71
0
Order By: Relevance
“…There is conflicting evidence in the literature on the effects of increased hepatic cholesteryl ester concentration on the secretion of VLDL. Wu et al [20] showed that a variety of manipulations which altered cholesteryl ester concentration in HepG2 cells had no effect on VLDL secretion, while Fungwe et al [13,21] have described a stimulation of VLDL formation in the livers of rats and hamsters fed cholesterol-enriched diets. Recent data from human subjects also emphasise the importance of available cholesterol in regulating VLDL secretion [22].…”
Section: Resultsmentioning
confidence: 99%
“…There is conflicting evidence in the literature on the effects of increased hepatic cholesteryl ester concentration on the secretion of VLDL. Wu et al [20] showed that a variety of manipulations which altered cholesteryl ester concentration in HepG2 cells had no effect on VLDL secretion, while Fungwe et al [13,21] have described a stimulation of VLDL formation in the livers of rats and hamsters fed cholesterol-enriched diets. Recent data from human subjects also emphasise the importance of available cholesterol in regulating VLDL secretion [22].…”
Section: Resultsmentioning
confidence: 99%
“…The intracellular mechanisms responsible for degradation of nascent apoB chains have been the subject of intense investigation in the past few years (5, 6, 9 -30, 35). Many recent reports have shown evidence for the involvement of the proteasome in the co-translational degradation of apoB in HepG2 cells (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). This evidence includes the sensitivity of apoB degradation to various proteasome inhibitors (12, 13, 15, 18 -22), the detection of ubiquitinated apoB (12, 18 -20, 22), and more recently the association of ubiquitinated apoB with the Sec61 complex of the translocon (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have reported that the apoB associated with luminal lipoproteins is also degraded post-translationally by an ALLN-sensitive degradation mechanism and could be rescued from degradation by cytosolic factors and metabolic energy, perhaps by inducing transport of apoB out of the degradation compartment (30). Furthermore, Wu et al (14) have reported a two-site model for the degradation of apoB in HepG2 cells, suggesting that after the initial rapid degradation process, apoB that is fully translocated into the ER lumen can still undergo degradation via a second proteolytic system that is ALLN-resistant but sensitive to DTT.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have shown that apoB can be marked for degradation by the ubiquitin-proteasome pathway even during its translocation into the ER (18 -20). ApoB can also enter other routes of intracellular degradation in hepatic cells (21,22). Remarkably, some molecules of ubiquitin-conjugated apoB can be rescued from degradation and secreted when hepatocytes are treated with lipids (23).…”
mentioning
confidence: 99%